Critical Disaster Studies - Remes, Jacob A. C. (Critical Studies in Risk and Disaster Ser., 2021)
Scholars from seven disciplines, whose work spans five continents, announce a new way of seeing disasters that is essential for making sense of our time: critical disaster studies. Critical Disaster Studies strips away the technocratic veneer that too often makes structural problems appear to be acute emergencies.